Solos com diferentes sistemas de manejo e rotação de culturas em longo prazo: flutuações nas frações de fósforo - Fornari, Mayara Regina (2017)
An exploration for economical and sustainable alternatives, to maximize the use of phosphorus present in soil has emphasized against the decline in phosphate fertilizer production reserves. Different physical and chemical characteristics of the soil can be affected by soil preparation and planting of different crops in crop rotation system. However, their effects on soil phosphorus dynamics are not fully clarified, especially in highly weathered regions such as southern Brazil.The objective of this work was to evaluate the influence of the No Tillage System (NTS) and Conventional Tillage System (CTS), associated with different winter cover crops on phosphorus fractions in very clayey oxisol. The experimental area is located at the Experimental Station of the Agronomic Institute of Paraná, in Pato Branco−Paraná.The main plots were treated with different cover crops: ryegrass (Lolium multiflorum L.), rye (Secale cereale L.), common vetch (Vica sativa L.), hairy vetch (Vicia villosa Roth) + black oat (Avena strigosa Schreb), forage turnip (Raphanus sativus L.), wheat and fallow, while (Triticum aestivum L.), in subplots two soil preparation systems (NTS and CTS) were used.Soil samples were collected from 0 to 0.10m depthwith three distinct periods: corn post−harvest (2014-2015), flowering of cover crops (2015) and soybean flowering (2015-2016).The methodologies used for the analyzes were: potentially available P by Mehlich 1 and anion exchange resins (AER); stored P in soil microbial biomass (SMB) through fumigation with chloroform; NaOH (0.5 mol l−1) extractable P, total organic P (Po) by ignition at 550 ° C in muffle furnace and subsequent extraction with sulfuric acid; Total P (Ptotal) by the block digestion method; Total inorganic P (Pi) by difference between P Total and Po total.The NTS in relation to CTS had the highest averages of P extracted in all fractions analyzed.Wheat had the lowest averages of available P by Mehlich (7.9 mg kg−1) and P stored in the SMB (30.8 mg kg−1). The organic P (Po) in both SCC and SPD corresponded to 30% of total P. It was concluded that the cultivation of the soil no tillage with hibernal plants and with high yields of soil, part of the P inorganic applied can accumulate in the form of moderately labile organic.